The chrysomeline leaf beetles of Timor, Wallacea (Coleoptera: Chrysomelidae: Chrysomelinae) - Reid, Chris A. M. (Zootaxa, 2024)
The Chrysomelinae are reviewed for the island of Timor and comprise seven species. Two new species of Paropsis genus group are described, including their first-instar larvae: Paropsisterna tais new species and P. tatamailau new species. Records of Paropsisterna captiosa (Clark, 1865) and Paropsis manto Blackburn, 1899 on Timor are discussed and both shown to be misidentified, but they remain unidentified because all known specimens are female. Three additional Chrysomelinae are noted, including Phola octodecimguttata (Fabricius, 1781), new for Timor. A key is provided for identification of the known Timorese Chrysomelinae.